Pengaturan Pemilihan Bandesa Adat Secara Musyawarah Mufakat - Wijaya, Made Indra Suma; Yanti, A.A. Istri Eka Krisna (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 4 (2023), 2023)
After the formation of the Bali Provincial Regional Regulation Number 4 of 2019, there were regulations regarding the mechanism for selecting Traditional Village Heads, which had never previously been regulated in previous regional regulations. This article aims to examine and analyze the Arrangements for the Election of Traditional Village Villages by Deliberation and Consensus After the Establishment of Bali Province Regional Regulation Number 4 of 2019. This article uses normative legal research methods as a type of research, which is studied through a statutory approach, analysis of legal concepts, and also history. The results of the study show that the Arrangements for the Election of Traditional Bandesas After the Establishment of Bali Provincial Regulation Number 4 of 2019, which were carried out through a deliberation and consensus mechanism, resulted in legal uncertainty in the regulation of the election of Traditional Bandesas, because there were no strict sanctions or strict provisions prohibiting the election mechanism for Traditional Bandesas. not through consensus deliberation. Pasca terbentuknya Peraturan Daerah Provinsi Bali Nomor 4 Tahun 2019, terdapat pengaturan mengenai mekanisme pemilihan Bandesa Adat, yang sebelumnya tidak pernah diatur dalam perda sebelumnya. Artikel ini bertujuan untuk mengkaji dan menganalisis Pengaturan Pemilihan Bandesa Adat Secara Musyawarah Mufakat Pasca Terbentuknya Peraturan Daerah Provinsi Bali Nomor 4 Tahun 2019. Artikel ini memakai metode penelitian hukum normative sebagai jenis penelitian, yang dikaji melalui pendekatan perundang-undangan, analisis konsep hukum, dan juga sejarah. Hasil studi menunjukkan bahwa Pengaturan Pemilihan Bandesa Adat Pasca Terbentuknya Peraturan Daerah Provinsi Bali Nomor 4 Tahun 2019 yang dimana dilakukan melalui mekanisme musyawarah mufakat, mengakitbatkan ketidakpastian hukum dalam pengaturan pemilihan Bandesa Adat, oleh karena tidak terdapat sanksi tegas ataupun ketentuan tegas yang melarang mekanisme pemilihan Bandesa Adat tidak melalui musyawarah mufakat.